ASD IN CHILDHOOD: INCLUSIVE PRACTICES IN EARLY CHILDHOOD EDUCATION (International Seven Journal of Multidisciplinary, 2025)
This article addresses inclusive practices for children with Autism Spectrum Disorder (ASD) in early childhood education, highlighting the challenges and potential of this process. The bibliographical research analyzed current scientific literature discussing the school inclusion of children with ASD, teacher training, pedagogical adaptations, and the importance of collaborative work between families, schools, and health professionals. The results indicate that, despite legal and regulatory advances, difficulties persist related to insufficient teacher training, a lack of adequate materials, and the absence of specific institutional policies for serving these children. The need for structured school environments that offer safety and appropriate stimuli for the sensory and communicative characteristics of autism is highlighted. Play is highlighted as a fundamental tool for promoting socialization and emotional development, while the connection between school and family strengthens emotional and pedagogical support. Furthermore, the article emphasizes the importance of active listening, empathy, and ethical behavior among professionals, essential elements for building an inclusive school culture. Full inclusion involves not only physical access but also effective participation and respect for differences, constituting a collective commitment and ongoing challenge. Finally, this study reinforces that inclusive early childhood education is an indispensable path to promoting equity and citizenship, highlighting the need for investment in training, public policies, and sensitive pedagogical practices that value the uniqueness of each child with ASD.